Current Opinions on Alternative Reservoir Placement for Inflatable Penile Prosthesis among Members of the Sexual Medicine Society of North America. (16th May 2013) - Karpman, Edward; Sadeghi‐Nejad, Hossein; Henry, Gerard; Khera, Mohit; Morey, Allen F.
Abstract: Introduction: The Sexual Medicine Society of North America (SMSNA) includes as its members the most experienced prosthetic surgeons in North America who implant inflatable penile prostheses (IPPs). Obliteration of the space of Retzius (SOR) resulting from robotic‐assisted laparoscopic prostatectomy (RALP) is a growing concern that has prompted many surgeons to look for alternative locations for reservoir placement during IPP implantation. Aim: The aim of this article is to educate the community of prosthetic urologists about potential complications and alternative locations for IPP reservoir placement. Methods: A panel of high‐volume experienced prosthetic surgeons discussed their views on alternative IPP reservoir implantation during a symposium focused on this topic. After reviewing reservoir complications, physician members of the SMSNA in attendance were surveyed using an audience response system (ARS) to facilitate sharing of knowledge, opinions, and recommendations related to reservoir implantation. Main Outcome Measures: Six ARS questions were used to identify the percentages of SMSNA member physicians with concerns about traditional IPP reservoir placement and utilizing alternative reservoir placement (ARP), and the impact of changing practice patterns on patient safety. Results: A majority (81%) of experienced implant surgeons surveyed think that RALP sometimes or frequently makes traditional IPP reservoir placement more difficult. Placement of the reservoir in an alternative location is sometimes or frequently advantageous for patient safety. A vast majority (97%) of the 95 respondents indicated that ARP techniques should be included in physician training courses. Conclusions: Physicians have concerns about reservoir placement in the SOR in RALP patients, which may explain why ARP is popular among SMSNA members. Device manufacturers should support physician training that provides for ARP. Clinical outcomes in RALP patients are needed to better understand the risks and benefits, and define the ideal location of reservoir placement in this population.Karpman E, Sadeghi‐Nejad H, Henry G, Khera M, and Morey AF. Current opinions on alternative reservoir placement for inflatable penile prosthesis among members of the Sexual Medicine Society of North America. J Sex Med 2013;10:2115–2120.